REALIZING LEGAL PROTECTION FOR OUTSOURCING WORKERS THROUGH EMPLOYMENT SETTING SYNCHRONIZATION - Khairani K (Jurnal Dinamika Hukum, 2015)
Debating on the outsourcing existence in Law No.13 of 2003 regarding to Labor, is still continuing even though there has been a decision of Indonesia Constitutional Court (MK) who stated the rules that the content of Article 65 paragraph (7) and Article 66 paragraph (2) has been outlawed. The problems of this research are: How is the outsourcing concept of regulating in the labor law and the regulation of the labor minister No. 19 of 2012; and What effort to keep the outsourcing arrangement can provide legal protection for workers? This research use juridical normative method. The research finds that some of the concept is in contradiction with the 1945 constitution and another Law which is related to the protection of labor, and even with the other articles that exists in the Labor Law itself so thats the norm contains contradictio adconceptio. Therefore, the system of outsourcing that will be regulated should consider the principles of goof outsourcing governance. They are: legal protection, non-discrimination, worker as the subject not as an object, benefit and welfare, sustainable working relation, and the shifting of protection to the labor.    Keywords: Law Protection, Outsourcing setting, synchronization